Piscicultura em areas de mananciais: estudo de caso do Rio Toledo, Bacia Hidrográfica do Paraná 3 - Morsoleto, Felipe Misael da Silva (2024)
This study used geotechnologies and free software tools, such as Google Earth and QGIS, to plan the sustainable use of water resources in the Toledo River microbasin, in western Paraná. The research characterized the area's geomorphology, land use and occupation, and mapped 97 excavated ponds, mostly small, with a focus on the orderly expansion of fish farming. The microbasin, with flat relief and soil favorable to aquaculture, is essential for the region's public, industrial and agricultural supply. The study also analyzed the morphometry and hydrology of the Toledo River, estimating the input of Nitrogen and Phosphorus from fish farming. About 75% of the Nitrogen and 74% of the Total Phosphorus are concentrated in the area above the Water Treatment Plant. The inactivity of rainfall and fluviometric stations limits the analysis of the river's self-purification capacity, highlighting the importance of water planning for the efficient management of urban river basins.